Unplanned Purchases: The Influence of Sales Promotions on Impulse Buying - Shrestha, Arpan (Kshitiz Management Review, 2025)
This study examines the influence of sales promotion efforts on impulse buying behavior in retail stores in Nepal. It investigates various sales promotional tools deployed for FMCG and their effectiveness in triggering impulse buying. This study includes four basic sales promotional tools viz. price discount; coupon; buy one, get one free; and consumer sweepstake. These environmental stimuli are considered as independent variables to predict the impulse buying behavior of the consumers. Under the realm of deductive approach, a survey was conducted among retail shoppers using a structured questionnaire. The questionnaire was administered by 600 retail customers in Western Nepal with 550 valid responses. It was revealed that the price discounts encourage impulse buying, leading to increased spending and brand switching. Coupons, while not directly linked to impulse buying, enhance brand loyalty and may indirectly increase impulse purchases by driving in-store visits. The ‘buy one, get one free’ promotion shows a strong positive correlation with impulse buying due to customer excitement. Similarly, consumer sweepstakes also promote impulse buying by encouraging customers to try new products. These results highlight the effectiveness of various sales promotions in stimulating impulse buying behavior, providing valuable insights for retailers aiming to boost their sales.